What are some of the best practices in Education Service Delivery? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
The Education and Sports Sector is responsible for the delivery of equitable, relevant and quality education, training and sports services for all. A lot of progress is being registered in the sector in terms of improvement in education outcomes. For instance, in terms of access, the number of classrooms increased from 25,888 in FY 2015/16 to 27,726 in FY 2016/17, and the total enrollment improved by 4.7% from 8,264,317 (4,122,663 males; 4,141,654 females) in FY 2015/16 to 8,655,924 (4,294,473 males, 4,361,451 females) in FY 2016/17. However, despite these and other achievements registered, there are still a number of challenges implementers face during the delivery of education services. Several of these are related to adequacy and quality education infrastructure, monitoring and inspection of the education service, welfare of the education officers and collection of education related data, among others. Some education institutions have adopted innovative approaches to address theseissues. The policy brief highlights some good practices that have been noted over the years by the Budget Monitoring and Accountability Unit (BMAU).